ANALYSIS OF DELIVERY OF PATIENTS WITH TWO OR MORE PREVIOUS CAESAREAN SECTIONS - Nesterov, Vitaly Fedorovich; Malgina, Galina Borisovna; Dyakova, Maria Mikhailovna; Kayumova, Alena Vladimirovna; Denisov, Artem Alekseevich (Mother and Baby in Kuzbass, 2026)
The aim of the study was to investigate the epidemiological characteristics and condition of the uterine scar, as well as the characteristics of childbirth in patients with a history of two or more cesarean sections (CS).Materials and Methods. A retrospective analysis of childbirth cases in patients with one, two, and three cesarean sections in the Sverdlovsk region over a five-year period (2021-2025) was conducted. A total of 27116 birth histories were analyzed and divided into three groups: patients with one CS (n = 20496), patients with two CS (n = 5590), and patients with three or more CS (n = 1030). Scar condition (based on surgical records), the incidence of early and late complications, and characteristics of childbirth were assessed.Results. A 9.9% decrease in the proportion of patients with one uterine scar was found (2025 compared to 2021). A 19.2% increase in the proportion of patients with a history of three CS was also noted. The risk of uterine rupture with an increased number of CS in the anamnesis increases by three to eight times. This is associated with an increased proportion of uterine scar insufficiency after multiple operative deliveries. With each subsequent CS, the incidence of insufficiency of the scar in the subsequent pregnancy increases – OR 4.56; 95% CI [2.34-9.76]. An increase in the number of CS performed prior to the current pregnancy increases the risk of placenta accreta in subsequent pregnancies. With an increasing number of prior cesareans, the average duration of surgery and average blood loss were increased. Adhesions were three times more common in patients with three or more prior cesareans compared to one prior cesarean. Among intraoperative complications, bladder injury occurred more frequently in patients with two or more prior cesareans, requiring additional interventions, including the involvement of related specialists. Postpartum hemorrhage was twice as common in patients with three or more uterine scars. An analysis of postpartum morbidity revealed a trend toward an increasing proportion of purulent-septic complications with an increasing number of prior cesareans.Conclusion. Each subsequent cesarean section increases the risk of complications in subsequent pregnancies, especially with repeat abdominal deliveries. Childbirth in such patients should be performed in a highly qualified facility with access to related specialists.
Keywords: uterine scar; cesarean section; placenta accreta; uterine rupture; adhesions; bleeding; postpartum endometritis